Construction of time-dependent dynamical invariants: A new approach - Bertin, M. C.; Pimentel, B. M. [UNESP]; Ramirez, J. A. [UNESP] (American Institute of Physics (AIP), 2012)
We propose a new way to obtain polynomial dynamical invariants of the classical and quantum time-dependent harmonic oscillator from the equations of motion. We also establish relations between linear and quadratic invariants, and discuss how the quadratic invariant can be related to the Ermakov invariant. (C) 2012 American Institute of Physics. [http://dx.doi.org/10.1063/1.3702824]